Bangunan Sehat sebagai Penunjang Health Tourism di Bali - Nimas Sekarlangit (ATRIUM: Jurnal Arsitektur, 2023)
Title: Healthy Buildings as Supporting Health Tourism in Bali Bali is known as a tourist destination, and tourism in Bali has fallen due to COVID-19. The government plans to revive Bali tourism by establishing it as a health tourism destination. Support for health tourism is the healthy buildings that can minimise the transmission of COVID-19. In addition to health in tourist attractions, houses and areas where people live must also be healthy. The facilities in traditional Balinese villages have generally changed their function to become new buildings to accommodate the number of families and changes in activity patterns. These changes cause buildings to become unhealthy and impact the health of the village. Based on these problems, it is necessary to ask that healthy buildings in traditional Balinese villages can support health tourism. The research objective was to conduct an initial study of healthy buildings in traditional villages. The benefit of the research is preventing transmission of COVID-19 and other outbreaks that may occur in the Bali region. The research method is a literature study and observation. The study results are recommendations for repairing buildings in traditional villages to reduce the risk of transmission of the COVID-19 virus.